Highly effective photocatalytic radical reactions triggered by a photoactive metal-organic framework - Zhang, Deshan (2022)
On account of their inherent reactive properties, radical reactions play an important role in organic syntheses. The booming photochemistry provides a feasible approach to trigger the generation of radical intermediates in organic reaction processes. Thus, developing effective photocatalysts becomes the key step in radical reactions. In this work, the triphenylamine moiety with photoactivity is successfully embedded in a highly porous and stable metal-organic framework (MOF), and the obtained MOF, namely, Zr-TCA, naturally displays a photoactive property derived from the triphenylamine-based ligand. In photocatalytic studies, the triphenylamine-based Zr-TCA not only exhibits a high catalytic activity on the aerobic oxidation of sulfides via the generation of the superoxide radical anion (O2•-) under light irradiation but also shows good efficiency in the trifluoromethylation of arenes and heteroarenes by the formation of the trifluoromethyl radical (CF3•) as an intermediate. Moreover, the high performance of Zr-TCA can be well maintained over a wide range of substrates in these radical reactions, and the recycled Zr-TCA still retains its excellent photocatalytic activity. The high recyclability and catalytic efficiency to various substrates make the constructed triphenylamine-based Zr-TCA a promising photocatalyst in diverse radical reactions.